Increasing Competency 4C using The G-Suite Application for Education - Legowo, Budi; Kusharjanta, Bambang; Sutomo, Artono Dwijo; Mulyadi, Mulyadi; Wahyuningsih, Daru (International Journal of Active Learning, 2019)
4C competencies (Communication, Collaboration, Critical Thinking and Problem Solving, Creativity and Innovation) is the learning achievement needed at this time. Learning in the Industrial Revolution 4.0 era provides an opportunity to increase 4C competencies without space and time limits, by utilizing information and communication technology. This study aims to use the G-Suite for Education as a substitution of learning models and or strategies to improve 4C competence in the Wawasan Pedagogi Course in the Physics Study Program of Mathematics and Natural Science Faculty of Sebelas Maret University. The research mechanism includes two strand cycles, namely learning with a student-centered learning (SCL) approach as follows: 1). Classical and 2). Online using G-Suite for Education. Reflections from the two research cycles show students could  follow both classical (face-to-face) and online learning strategies, in the delivery of material and or assessment of learning outcomes.